Superemission of Cr nanolayers - Khmelinskii, Igor (2017)
We continue our studies of metal nanolayers started earlier [1]. Presently, we investigate absorption, emission and superemission in Cr nanolayers. We provide experimental estimates of the energy density and power density of superemission of Cr nanolayers, along with estimates of the diffraction-limited light divergence. We report that the divergence of the superemission along the direction normal to the nanolayer corresponds to that of a point source, with the divergence angle of ca. 0.2 rad. Additionally, we report surprising long-range transfer of the excitation energy in Cr metal films, at macroscopic distances of 1 cm. Published by Elsevier Ltd.